2022
DOI: 10.1371/journal.pone.0277394
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 vaccines in Italian public opinion: Identifying key issues using Twitter and Natural Language Processing

Abstract: The COVID-19 pandemic has changed society and people’s lives. The vaccination campaign started December 27th 2020 in Italy, together with most countries in the European Union. Social media platforms can offer relevant information about how citizens have experienced and perceived the availability of vaccines and the start of the vaccination campaign. This study aims to use machine learning methods to extract sentiments and topics relating to COVID-19 vaccination from Twitter. Between February and May 2021, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, the majority of previous works on opinions toward COVID-19 vaccination on social media have focused on a single location and a single language [9] , [11] , [12] . On the other hand, our study collects posts regardless of location and language.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the majority of previous works on opinions toward COVID-19 vaccination on social media have focused on a single location and a single language [9] , [11] , [12] . On the other hand, our study collects posts regardless of location and language.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of Stracqualursi and Agati [24] was to assess public opinion and perception on COVID-19 vaccines in Italy using 71,000 tweets containing vaccines-related keywords from Italian Twitter users, over the period February 1st to May 31st 2021. To determine the prevalent sentiment, spatial and temporal sentiment analysis was performed using VADER, and findings showed that sentiment fluctuations were highly influenced by news of vaccines’ side effects.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, the trends observed within this set of keywords are also reflected in the analysis provided in the following sections. [23], construction of cohorts of similar patients [24], processing of electronic medical records [25], understanding of patient's answers in a French medical chatbot [26]; • German: evaluation of Transformers on clinical notes [27]; • Greek: improving the performance of localized healthcare virtual assistants [28]; • Hindi: classification of COVID-19 texts [29], chatbot for information sexual and reproductive health for young people [30]; • Italian: analysis of social media for quality of life in Parkinson's patients [31], sentiment analysis of opinion on COVID-19 vaccines [32,33], estimation of the incidence of infectious disease cases [34]; • Japanese: understanding psychiatric illness [35], detection of adverse events from narrative clinical documents [36]; • Korean: BERT model for processing med-ical documents [37], sentiment analysis of tweets about COVID-19 vaccines [38];…”
Section: Analysis Of Abstract From Publicationsmentioning
confidence: 99%